Identification of dysregulated lipid metabolic pathways in mouse embryonic derived neurons and in a mouse model of Alzheimer's disease: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Costa, Ana Paula; Menon, Vilas; McIntire, Laura Beth
Abstract: Background: Lipidomic data from autopsy brain, human plasma and animal models highlights severe lipid dyshomeostasis in Alzheimer's disease (AD). The importance of lipid metabolism in AD is supported by GWAS studies which have identified multiple lipid modifying enzymes and interacting proteins. Further, mouse genetic studies have shown benefit of genetic disruption of synaptojanin1 (Synj1), phospholipase A2 (PLA2), and phospholipase D2 (PLD2). Method: We used high‐content screening for Aß‐triggered synapse loss in mouse embryonic stem cell derived neurons to identify phospholipid modifying enzymes which contributed to synapse loss. In an orthogonal approach we used DESI Imaging Mass Spectrometry to identify lipid metabolic pathways which are dysregulated in brain of a mouse model of AD. Result: We showed that haploinsufficiency of Synj1, a phosphoinositide phosphatase, and concurrent maintenance of phosphoinositide levels, ameliorated behavioral deficits in a mouse model of AD in spite of pathological amyloid accumulation. Similarly, disruption of phospholipid modifying enzymes PLD2 and PLA2 resulted in rescue of behavioral deficits despite the pathological accumulation of amyloid. It is likely then that specific pathways in lipid metabolism underlie AD disease mechanisms leading to behavioral impairment. Specifically, the loss of polyunsaturated fatty acids among multiple phospholipid classes is common in AD affected human brain and mouse models. Our lipidomic studies show that lipid species are dramatically altered in mouse brain in a regionally specific manner determined by imaging mass spectrometry. Conclusion: Synthesis of these findings and the fact that disruption of phospholipid modifying enzymes Synj1, PLA2 and PLD2 rescue behavioral deficits in spite of pathological accumulation of amyloid, implicate acyl chain remodeling as a candidate therapeutic target in AD.